Didactic potential of metaphors used in medical discourse - Karska, Katarzyna; Prażmo, Ewelina (LingBaW. Linguistics Beyond and Within, 2017)
Specialist languages should be straightforward and unambiguous. In areas such as law, business or medicine precision and to-the-point wording is required. However, in order to facilitate the description of complicated matters, and especially in expert to non-expert communication, unexpected strategies, e.g. metaphorisation, are used. Conceptual metaphor theory, as initially introduced by Lakoff and Johnson (cf. Lakoff & Johnson, 1980) states that human beings tend to think in metaphors, i.e. we are engaged in constant search of similarities between concepts. This drive for pattern recognition helps us understand the unknown in terms of the familiar, the abstract in terms of the concrete. Most conceptual metaphors are grounded in our physical experience of the world, which means that we draw from this familiar experience while creating metaphorical mappings to the complex, abstract concepts. Controversial as it may seem, the same process applies to understanding professional terms and scientific notions, and as a result the language of law, business, medicine, etc. is heavily metaphorical in nature. In our presentation we focus on medicine alone and analyse a corpus of medical text in search of conceptual metaphors. We claim, that rather than obscuring the message, metaphors actually make it clearer and more precise. They enrich conceptualisation, structure the semantics of the message and serve a number of pragmatic functions, esp. in doctor to patient communication. By choosing a certain metaphor, the message may e.g. be softened in order to lessen the impact it has on the recipient. Moreover, it may be more easily understood if it is built on an adequate conceptual metaphor. Many metaphors used in the medical discourse are based on multimodal representations e.g. descriptions of diseases often invoke the imagery of food including its shape, colour, texture, and smell. Such multimodality of representation (cf. Forceville, 2009 and online) engages a number of cognitive faculties for the construction of a complex conceptualisation and in this way helps us gain better understanding of the concepts described. We claim that conceptual metaphor and esp. pictorial metaphor is a very effective tool used in didactics and its use is perfectly justified in scientific discourses, including the medical discourse. Therefore, in our presentation we analyse pictorial metaphors found in medical discourse and in the field of radiology in particular.